Efeito da suplementação de ômega-3 no estado nutricional de pacientes com câncer de pâncreas: uma revisão sistemática de ensaios clínicos - Pires, Luciana Bicalho Cevolani (2023)
Introduction: pancreatic neoplasm is the seventh leading cause of cancer death worldwide. Most of these patients with pancreatic neoplasm develop malnutrition that can progress to cachexia. Although omega-3 supplementation is used in clinical practice, however, so far, evidence on omega-3 fatty acid supplementation on nutritional status in patients with pancreatic cancer has not been summarized by any systematic review yet. Objective: to synthesize and evaluating the evidence on the effects of omega-3 supplementation on the nutritional status of patients with pancreatic cancer. Methods: a systematic review of clinical trials was performed with high compliance with the Preferred Reporting Items for Systematic Reviews and MetaAnalyses (PRISMA Statement 2020). MEDLINE/PubMed, EMBASE, Cochrane Central Register of Controlled Trials (CENTRAL), Scopus, and Web of Science were searched, with no restrictions on publication date and language. The internal validity and risk of bias of randomized controlled trials were assessed using the revised RiskOf-Bias (RoB 2) tool for randomized controlled trials, while the risk of bias in nonrandomised intervention studies was assessed using the Risk tool tool Of Bias In Nonrandomized Studies of Interventions (ROBINS-I). Results: eight studies met all inclusion criteria and were analyzed. Five studies were randomized clinical trials and most of them (n = 4) were classified as low risk of bias, and the three quasi-experiments were classified as moderate risk of bias. Among the studies that investigated the outcome increase/maintenance of body weight, six presented positive and statistically significant results (p<0.05). Conclusion: in conclusion, the evidence presented indicates that omega-3 supplementation in patients with pancreatic cancer is safe, well tolerated and beneficial, due to stabilization or increase in body weight, decrease in IL6 production, decrease in cortisol/ insulin and CRP stabilization, and these changes occurred in association with improved appetite and reduced levels of inflammatory biomarkers. PROSPERO registration: CRD42022332619.